Solvothermal synthesis of nano-CeO 2 and degradation of dye in indoor lighting. (21st April 2014) - Zhao, Bin; Gu, Mingjie; Li, Chengqiang; Song, Xiaozhen; Li, Ruixing
Azo dyes are an abundant class of synthetic, organic compounds containing one or more azo bonds (-N=N-). A large amount of these dyes are produced for using in different applications. However, their complex structure makes them difficult to biologically degrade. We sought to degrade acid orange 7 (AO7) using nitrogen-doped (N-doped) and carbon-nitrogen (C-N) co-doped nano-CeO2 . N-doped monocrystalline CeO2 nanoparticles was synthesised by solvothermal method using triethanolamine as a nitrogen source at 120°C for 24 h. C-N co-doped monocrystalline CeO2 nanoparticles were synthesised by solvothermal method using hexamethylenetetramine as both nitrogen and carbon source at 140°C for 24 h. For purposes of comparison, a sample of undoped CeO2 was synthesised using the dopant of neither triethanolamine nor hexamethylenetetramine. The doped and undoped CeO2 monocrystals were all less than 10 nm in diameter. Nitrogen and carbon-nitrogen were shown to be incorporated into CeO2 lattice from the results of both XRD and X-ray photoelectron spectroscopy analyses. The degradation of AO7 in water was investigated using a domestic 10 W compact fluorescent lamp. The results showed the degradation ratios of AO7 in the presence of nano-CeO2 in the sequence of: C-N co-doped CeO2 ≯ N-doped CeO2 ≯≯ undoped CeO2, corresponding to magnitudes of 98.8%, 97.6%, and 48.2%, respectively.